Analisis Makna Metafora Pada Lirik Lagu Nadin Amizah â€œSorak Soraiâ€ - Nurashri Shafary (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
One way to express feelings is to write them into a song lyric that is full of meaning. Nadin Amizah created the song